Profiling and cheminformatics bioprospection of curcurbitacin I and momordin Ic from Momordica balsamina on α-amylase and α-glucosidase - Viruska Jaichand; Adedayo Ayodeji Lanrewaju; Himansu Baijnath; Saheed Sabiu; Viresh Mohanlall (Journal of Enzyme Inhibition and Medicinal Chemistry)
Momordica spp. has been traditionally used to manage type 2 diabetes mellitus, but the mechanisms and metabolites remain unclear. This study evaluated the inhibitory potential of Momordica balsamina extracts on α-amylase and α-glucosidase in vitro, identifying cucurbitacin I and momordin Ic via high-performance liquid chromatography-photo diode array, and their inhibitory potential in silico. Ethyl acetate seed extract (14.46 µg/ml) and hexane fruit flesh extract (16.79 µg/ml) exhibited lower IC50 values against α-amylase and α-glucosidase, respectively, compared to acarbose (reference standard). Comparatively, momordin Ic concentrations (36.57–605.98 µg/ml) were higher than cucurbitacin I (17.08–44.34 µg/ml). A 140 ns simulation showed that cucurbitacin I (−63.06 kcal/mol) and momordin Ic (−66.53 kcal/mol) exhibited stronger binding to α-amylase than acarbose (−36.46 kcal/mol), whereas cucurbitacin I (−38.08 kcal/mol) and momordin Ic (−54.87 kcal/mol) displayed weaker binding to α-glucosidase, relative to acarbose (−63.73 kcal/mol). Generally, momordin Ic demonstrated better thermodynamic properties, hence further in vitro and in vivo studies are needed to validate their antidiabetic potential.